2018
DOI: 10.4274/tjod.87269
|View full text |Cite
|
Sign up to set email alerts
|

The effect of first trimester hemoglobin levels on pregnancy outcomes

Abstract: Objective:The relationship between hemoglobin levels and pregnancy outcomes is still a challenging issue. There is a supported opinion about the increased adverse pregnancy outcomes both with low and high hemoglobin levels. In this study, we aimed to evaluate this association for first trimester hemoglobin levels in a Turkish population.Materials and Methods:In this retrospective study, 1306 women who were followed up during their pregnancy and gave birth in our clinic were enrolled. The patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
9
1
1
Order By: Relevance
“…of pregnant women with thalassemia. In our study, we did not nd signi cant differences between maternal and fetal pregnancy outcomes in the three different Hb concentrations subgroups of the control group, which was not the same as previous ndings [22,36] . However, the incidence of GDM in Hb ≥ 130 g/L subgroup was signi cantly higher comparing with Hb < 110 g/L and 110 ≤ Hb < 130 g/L subgroups in pregnant women with thalassemia minor.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…of pregnant women with thalassemia. In our study, we did not nd signi cant differences between maternal and fetal pregnancy outcomes in the three different Hb concentrations subgroups of the control group, which was not the same as previous ndings [22,36] . However, the incidence of GDM in Hb ≥ 130 g/L subgroup was signi cantly higher comparing with Hb < 110 g/L and 110 ≤ Hb < 130 g/L subgroups in pregnant women with thalassemia minor.…”
Section: Discussioncontrasting
confidence: 61%
“…Its measurement is a routine standard test for evaluating physical status among pregnant women in their rst visit to primary health care clinics. Anemia is often a concern, which may lead to adverse pregnancy outcomes, including low birth weight, postpartum hemorrhage, cesarean section, and preterm birth [21,22] . However, insu cient attention has been paid to high maternal Hb.…”
Section: Introductionmentioning
confidence: 99%
“…All hemoglobin measurements were obtained prepartum, which ensured hemoglobin measurements were not a consequence of peri- and/or postpartum bleeding. Twenty-two of these studies defined anemia using the WHO-conformant threshold of <11 g/dl (Table 1), 9,10,12,14,16,3046 the other 24 studies fell into the Lower or Unspecified Threshold groups and were analyzed separately (Table 2). 11,13,15,4767…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also investigated whether when anaemia appears in the pregnancy is associated with adverse outcomes. For example, some studies found a significant association of first‐trimester anaemia with adverse pregnancy outcomes, 9 whereas others found significant associations only in the second or third trimesters 8,10 . There is reasonable agreement that the severity of anaemia, especially when moderate or severe, is most strongly related to adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%